2007
DOI: 10.1007/s00402-007-0518-1
|View full text |Cite
|
Sign up to set email alerts
|

Timing of thoracolomber spine stabilization in trauma patients; impact on neurological outcome and clinical course. A real prospective (rct) randomized controlled study

Abstract: Early surgery may improve neurological recovery and decrease hospitalization time and also additional systemic complications in patients with thoracolumbar spinal cord injuries. Thus early stabilization of thoracolumbar spine fractures within 8 h after trauma appears to be favorable.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
138
1
3

Year Published

2011
2011
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 148 publications
(150 citation statements)
references
References 29 publications
4
138
1
3
Order By: Relevance
“…The risks include aggravating secondary injury by hypotensive episodes or blood loss. Several studies point out that patients should be treated with early surgery if medically stable to do so [2,11]. Clinical benefits of early surgery possibly include shorter length of both ICU and overall hospital stay with fewer medical complications (such as pneumonia and DVT) [60].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…The risks include aggravating secondary injury by hypotensive episodes or blood loss. Several studies point out that patients should be treated with early surgery if medically stable to do so [2,11]. Clinical benefits of early surgery possibly include shorter length of both ICU and overall hospital stay with fewer medical complications (such as pneumonia and DVT) [60].…”
Section: Discussionmentioning
confidence: 99%
“…This measurement considers not only the severity of injury, but also the accessibility of the medical system at stabilizing the patient and allowing them to proceed with rehabilitation. Of the 22 clinical studies identified in this review, nine Level III studies measured the length of stay [7,11,14,16,27,32,37,40,42,52]. Early surgical decompression was associated with a shorter hospital length of stay in eight studies [7,14,16,27,32,37,40,42] (although Guest et al [27] reported no p values), whereas the other only recorded the length of stay in the ICU [52].…”
Section: Histopathologic Correlationmentioning
confidence: 99%
See 2 more Smart Citations
“…Early surgery does not appear to be associated with an increased rate of complications [99]. However, clinical evidence for increased neurological recovery remains, at best, tenuous based on the existing trials [100][101][102][103][104].…”
Section: Decompression Strategiesmentioning
confidence: 99%